Applying novel eco-exergoenvironmental toxicity index to select the best irrigation system of sunflower production. (1st July 2022) - Khanali, Majid; Ghasemi-Mobtaker, Hassan; Varmazyar, Hossein; Mohammadkashi, Naghmeh; Chau, Kwok-wing; Nabavi-Pelesaraei, Ashkan
Abstract: The goal of this study is to create a novel eco-exergoenvironmental toxicity index to identify the most sustainable irrigation system among surface irrigation and drip irrigation for sunflower production in Kurdistan, Iran. This research emphasizes on choosing a sustainable irrigation agricultural system with an invented index, which considers all aspects. For this purpose, life cycle assessment (USEtox 2.0) is applied for evaluating toxicity factors and results show that the environmental situation of drip irrigation is better than that of surface irrigation. Exergy analysis results reveal that total exergy demands are 287, 421 and 211, 458 Megajoule per ten ton of sunflower for surface irrigation and drip irrigation scenarios, respectively. Nitrogen has the highest share (more than 50%) in all factors and exergy categories. Eco-efficiency of all toxicity factors of drip irrigation (with net profit 7417.86) is more than those of surface irrigation (with net profit 6614.35). The analytic hierarchy process analysis indicates that human toxicity, cancer has the first rank of priority based on expert choices. Based on the novel index results, sustainable rates are 1.690 and 1.169 for surface irrigation and drip irrigation, respectively. Thus, drip irrigation is an eco-exergoenvironmental-friendly scenario in comparison to surface irrigation. Graphical abstract: Image 1 Highlights: Eco-Exergoenvironmental toxicity index is created for comprehensive suitability assessment. LCA of surface and drip irrigation systems is investigated by USEtox 2.0. CExD and Eco-efficiency are applied for energy and economical investigation. Nitrogen is the main hotspot in all environmental toxicity and exergy categories. Drip irrigation is the most sustainable irrigation system with EET of 1.169.